Optimalisasi Peran Dandim 1301/Sangihe dalam Penanganan Erupsi Gunung Api Ruang Guna Mendukung Tugas Pokok TNI AD - Roy Astyanto; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the optimization of the role of Dandim 1301/Sangihe in handling the eruption of Mount Ruang as part of the implementation of the Indonesian Army’s (TNI AD) main duties in the field of Military Operations Other Than War (OMSP). The research was conducted in Sitaro Regency, North Sulawesi, using a qualitative approach with purposive sampling techniques. The informants consisted of personnel from Kodim 1301/Sangihe, BPBD staff, and community leaders. Data was collected through interviews, observations, and documentary studies. The results show that the role of Dandim is crucial in coordinating and mobilizing disaster response, but there are still challenges such as limited personnel, logistics, equipment, and weak inter-institutional coordination. The study concludes that optimization can be achieved through the development of a disaster risk map, strengthening inter-institutional collaboration, utilizing technology (drones), and conducting routine disaster training and simulations. These measures are expected to improve the effectiveness and speed of response in facing volcanic eruptions.